Communication Aspects in Health Care Work in Nepal - Bakke, Marit; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2008)
The aim of this article is to describe the communication aspects in health care work in Nepal. It begins with the idea that communication is important in social development and covers some facts about health conditions and health services in Nepal. It gives a brief introduction to different development paradigms as well as an assessment of their relevance for social change and some basic principles in communication theory. The article then describes communication strategies in which people get a chance to express cultural beliefs with respect to health and treatment practices, and how this knowledge can be applied to facilitate increased use of health services. Cultural conceptions play a crucial role in successful health communication. The article gives one illustration of this by presenting the terms used by mothers in five different ethnic groups in Nepal to describe acute respiratory infections (ARI) and illnesses among children. Implications for health communication are presented at the end of this article. Key Words: Health Communication, Communication theory, Cultural Preconditions, Cultural Strategy, Social Development DOI = 10.3126/dsaj.v2i0.1358 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.65-100